Enhanced cyber security with IBM Spectrum Scale and IBM QRadar : accurately detecting and prioritizing threats to your data - Chakrabarty, Boudhayan (IBM redpaper., 2019)
Having appropriate storage for hosting business-critical data and advanced Security Information and Event Management software for deep inspection, detection, and prioritization of threats has become a necessity of any business. This IBM® Redpaper publication explains how the storage features of IBM Spectrum® Scale, combined with the log analysis, deep inspection, and detection of threats provided by IBM QRadar®, helps reduce the impact of incidents on business data. Such integration provides an excellent platform for hosting unstructured business data that is subject to regulatory compliance requirements. This paper describes how IBM Spectrum Scale file audit logging can be integrated with IBM QRadar. Using QRadar, an administrator can monitor, inspect, detect, and derive insights for identifying potential threats to the data stored on IBM Spectrum Scale. When the threats are identified, you can quickly act on them to mitigate or reduce the impact of incidents. This paper is intended for chief technology officers, solution engineers, security architects, and systems administrators. NOTE: This paper assumes a basic understanding of IBM Spectrum Scale, IBM QRadar, and their administration.